2013
DOI: 10.1371/journal.pone.0060288
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Design of Regulatory Elements Based on High-Precision Strength Prediction Using Artificial Neural Network

Abstract: Accurate and controllable regulatory elements such as promoters and ribosome binding sites (RBSs) are indispensable tools to quantitatively regulate gene expression for rational pathway engineering. Therefore, de novo designing regulatory elements is brought back to the forefront of synthetic biology research. Here we developed a quantitative design method for regulatory elements based on strength prediction using artificial neural network (ANN). One hundred mutated Trc promoter & RBS sequences, which were fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 41 publications
0
75
0
1
Order By: Relevance
“…A more detailed understanding of the functionality of the alternative promoters in cisplatin resistance is likely to have other applications; for example, it may be possible to design novel anticancer drugs that interact with specific promoter sequences, e.g., G-rich sequences which may form DNA G-quadruplexes (40)(41)(42). In addition, future research may make use of novel synthetic biology methods to build molecular models of various components of alternative promoters (43)(44)(45)(46) to overcome drug resistance and enable more effective and personalized cancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…A more detailed understanding of the functionality of the alternative promoters in cisplatin resistance is likely to have other applications; for example, it may be possible to design novel anticancer drugs that interact with specific promoter sequences, e.g., G-rich sequences which may form DNA G-quadruplexes (40)(41)(42). In addition, future research may make use of novel synthetic biology methods to build molecular models of various components of alternative promoters (43)(44)(45)(46) to overcome drug resistance and enable more effective and personalized cancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…However, since position weight matrix models are highly reliant on experimental data obtained from promoter-strength studies, they are only applicable to well-studied micro-organisms, such as E. coli. Other models have also been developed to predict promoter strengths based on the partial least squares [107] and artificial neural network [108] methods among other methods. Computation models have been used for the de novo design of synthetic promoters to fine-tune the enzyme genes involved in the deoxyxylulose phosphate pathway in E. coli [108].…”
Section: Promoters For Tuningmentioning
confidence: 99%
“…Several kernel functions including the polynomial function, sigmoid function, and radial basis function (RBF) were tried one-by-one in preliminary experiments, and found that the RBF is most suitable for fitting the data. A mutation library containing 100 promoter sequences and their corresponding strength values [8] was randomly divided into a training set and a test set for training and test of the SVM models, respectively. Different amount of sequences (from 10 to 90) were tried one-by-one to determine the minimum size of training set for reaching the best prediction performance.…”
Section: I) Mean Squared Error (Mse)mentioning
confidence: 99%